Whole-systems assessment of the value of energy storage in low-carbon electricity systems - Pudjianto,D; Aunedi,M; Djapic,P; Strbac,G (IEEE Transactions on Smart Grid, 2014)
Energy storage represents one of the key enabling technologies to facilitate an efficient system integration of intermittent renewable generation and electrified transport and heating demand. This paper presents a novel whole-systems approach to valuing the contribution of grid-scale electricity storage. This approach simultaneously optimizes investment into new generation, network and storage capacity, while minimising system operation cost, and also considering reserve and security requirements. Case studies on the system of Great Britain (GB) with high share of renewable generation demonstrate that energy storage can simultaneously bring benefits to several sectors, including generation, transmission and distribution, while supporting real-time system balancing. The analysis distinguishes between bulk and distributed storage applications, while also considering the competition against other technologies, such as flexible generation, interconnection and demand-side response.